ANALYSIS OF THE EXPORT COMPETITIVENESS OF INDONESIAN ARECA NUTS TO THE UNITED ARAB EMIRATES - Fery Putra Alam Bara Munthe; Rulianda P Wibowo; Tavi Supriana (CV. Radja Publika, 2025)
This study aims to analyze the export competitiveness of Indonesian areca nut to the United Arab Emirates (UAE). The objective of the research is to evaluate the comparative advantage of Indonesian areca nut exports compared to other exporting countries such as India, Myanmar, Malaysia, and Thailand from 2013 to 2023 using the Revealed Comparative Advantage (RCA) method. The study uses secondary data collected from Trademap and UN Comtrade, focusing on the value and volume of areca nut exports. The results indicate that Indonesia has a relatively strong export competitiveness, as shown by RCA values consistently above 1 in several years. However, Indonesia faces competition from Myanmar and Thailand, which also demonstrate significant comparative advantages. The findings suggest that the Indonesian government should focus on improving export policies, ensuring product quality, and expanding market access to sustain and improve the competitiveness of Indonesian areca nut in the UAE market.